The influence of the manufacturing constraints on the optimal design of laminated conical shells. (1st March 2020) - Stawiarski, Adam; Chwał, Małgorzata; Barski, Marek; Muc, Aleksander
Abstract: The current paper deals with the impact of geometrical and material parameters of the laminated conical shell on the load carrying capacity based on the finite element analysis. Various parameters were taken into account, that is, stiffness ratio, cone angle or shell height. Moreover, the mechanical behavior of conical shell having the concave and convex imperfections has been studied. Presented results confirmed the reduction of the buckling load with an increase of the cone angle connected with the rise in the base of the cone. The originality in this area is determining the approximately constant optimal initial fiber orientation even with the assumption of variable thickness and fiber orientation. Moreover, the results evidently showed that for a high value of cone angle the comparable value of the buckling load was obtained for a relatively wide range of the fiber orientations. The detailed analysis of the buckling modes for the particular structure is crucial from the optimization point of view.